Antecedents of Generation Y consumers’ perceived value of social media advertisements - Marko van Deventer; Marcelle Saraiva (Cogent Social Sciences)
This study investigates the perceived value of social media advertisements among Generation Y consumers in South Africa, focusing on the antecedents of informativeness, entertainment, irritation, and credibility. The significance of the study lies in its exploration of how these factors influence the effectiveness of social media advertising, providing insights for marketers aiming to engage this important and sizeable demographic effectively. The data collected from 430 Generation Y consumers through self-administered questionnaires was analysed using a variety of statistical techniques, in particular confirmatory factor analysis and path analysis. These techniques were used to validate the data and examine the relationships between the studied latent factors. The path analysis results indicate that informativeness, entertainment, and credibility are positively associated with the value perceptions of social media advertisements among the studied participants, while irritation is negatively associated. The study suggests that marketers should focus on creating informative and entertaining content to enhance the perceived value of their social media advertisements. Additionally, reducing irritating elements and maintaining credibility are crucial for maintaining positive consumer perceptions. These strategies can help marketers craft more effective social media advertisements, leading to better engagement and improved marketing outcomes.